The Invisible Curriculum That Shapes Character: A PRISMA-Based Systematic Review of Hidden Curriculum in Elementary Schools - Okta Vitriani; Sukiman (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2026)
This study aims to analyze the role of hidden curriculum in the character education of elementary school students through the Systematic Literature Review approach based on the PRISMA protocol. Data was collected from Scopus, ERIC, and Google Scholar as of June 7, 2026 using a title-abs-key search strategy, with a total of 136 initial articles filtered into 26, then 15 at the eligibility stage, and finally 11 articles that met the inclusion criteria. The results of the study show that the hidden curriculum is implemented through habituation of religious activities, teacher examples, discipline culture, as well as social interaction and extracurricular activities that are integrated into school culture. The practice contributes to the formation of characters such as discipline, religious, responsibility, social concern, honesty, and creativity which are reflected in the changes in students' daily behavior. However, its effectiveness varies depending on contextual factors such as teacher consistency, school culture, and family support. The relationship between hidden curriculum practices and behavioral changes is implicit causal through habituation, modeling, and social reinforcement mechanisms. These findings imply that educators and policymakers need to institutionalize the hidden curriculum through strengthening school culture, teacher exemplary training, and integration in systematic character education programs.